ELECTROTECHNOLOGIES SUPPORTING OF DIELECTRIC PLANT MATERIAL PROCESSING - Sumorek, Andrzej (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The article has a review character. The characteristics of the two electrotechnologies developed by Department of Computer and Electrical Engineering is described ie. convective drying in the presence of an electric field and dust removal using bifilar filters. This article presents selected results describing the energy savings resulting from the application of these technologies.